Profil DNA Forensik pada Barang Bukti Dua Kasus Pembunuhan di Indonesia - RIANTI, PUJI; CRISTIN, ELISA; WIDODO, PUTUT TJAHJO (Departemen Biologi, Institut Pertanian Bogor, 2018)
DNA technology for profiling purposes has been used in many basic and applied science. One of the emerged applied science in genetics is it’s uses in solving crime cases. Homicide became one of highest crime cases in Indonesia. Solving its cases through DNA profiling technology using items of evidence as tool is needed. Here, we report the profiling of human DNA from several items of evidence available in the crime scene and the suspect. We used items of evidence from study cases no. 18098 and 18101, based on the legal permission of Indonesia’s National Police. We used 21 international standards of human STR markers, one sex-determining marker, one Y STR marker, and one independent Y marker to developed human alleles from tissue and blood stains left and/or shred on the victims, soap bottles, knifes, victim’s clothes and ropes as well as the buccal swab of the crime suspect. Our alleles identification matched between the victim and the crime suspect in both cases with the accuracy of DNA profiles compatibility at 99.99%. Detection of DNA profiling is depending on the evidence and time of storage which are influence by environment that can lead to the process of decayed and/or contaminated.